Cardiac toxicity events in the PHARE trial, an adjuvant trastuzumab randomised phase III study. Issue 13 (September 2015) - Pivot, Xavier; Suter, Thomas; Nabholtz, Jean Marc; Pierga, Jean Yves; Espie, Marc; Lortholary, Alain; Khayat, David; Pauporte, Iris; Romieu, Gilles; Kramar, Andrew; Fumoleau, Pierre
Abstract Background This article reports, the cardiac toxicity according to 6- versus 12-month durations of adjuvant trastuzumab in PHARE randomised trial (NCT00381901). Patients and methods Cardiac follow-up and Left Ventricular Ejection Fraction (LVEF) assessment by echocardiography or multigated acquisition scan were performed every 3 months while patients received trastuzumab and after completion of treatment over the first 2 years and every 6 months afterwards. The primary cardiac end-point was Cardiac Heart Failure (CHF) defined as New York Heart Association (NYHA) class III or IV. The secondary cardiac end-points were: cardiac events, cardiac dysfunctions defined by NYHA class I and II; LVEF decreases, cardiac recoveries. The cardiac subcommittee reviewed cardiac events and assessed if patients had favourable outcomes or not on the basis of trends from LVEF measurements. Results Among 3380 patients the cardiac dysfunction assessment included 14, 055 and 13, 218 LVEF measurements in the 12- and 6-month arms. The overall incidences of CHF were 0.65% (11/1690) and 0.53% (9/1690) in the 12 and 6 month arms, respectively (p > 0.05). Cardiac dysfunction occurred in 5.9% (100/1690) and 3.4% (58/1690) of patients in the 12 and 6 month arms, respectively (p = 0.001). Recoveries were observed for the majority patients and 0.79% (27/3380) of patients experienced an unfavourable cardiac outcome. Conclusion PHARE confirm that the incidence of cardiac end-points remains low and mostly reversible after trastuzumab. Identification at baseline of cardiac risk categories of patients should be of interest to provide an optimal adaptation of adjuvant modalities and a shorter duration might be an option.